Some results on a question of Li, Yi and Li - BANERJEE , Abhijit; MAJUMDER , Sujoy (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
The purpose of this paper is to study the uniqueness problems of certain difference polynomials of meromorphic functions sharing a nonzero polynomial. The results of this paper improve and generalize some recent results due to Li, Yi and Li [11]. Some examples have been exhibited to show that some conditions used in the paper are sharp. Mathematics Subject Classification (2010): 30D35.